Agreements on production section in Kazakhstan: current state, problems, solutions. (Journal of Economic Research & Business Administration, 2015)
Kazakhstan's oil and gas industry continues to evolve , increasing the rate of production , maintains the high investment attractiveness. Favorable factor for this purpose is the positive dynamics of the global oil and gas market , which causes enhanced sales in foreign markets and the existence of liquidity available for investment in research and production. However, the extraction of hydrocarbons is tremendous pressure on the environment, so the issues of the economi mechanism subsoil are relevant, require constant attention and analysis of key components to further improve the legal and fiscal framework. The article is devoted to the actual problem PSAs hydrocarbons considered positive and negative aspects for the state to enter into the Agreement on section (PSA) with mining companies in oil and gas, substantiated conclusions why public authorities decided to abandon in favor of PSA contracts include provisions Excess Profits tax (EPT contracts).
Keywords: subsurface use; contracts on subsurface use; the agreement on the section of production; the company subsoil users; a tax mode